Production of Oyster Mushroom on Different Substrates Using Cylindrical Block System (Progressive Agriculture, 2013)
The experiments were conducted at the Mushroom and Tissue Culture Laboratory, Horticulture Demonstration and Training Center (HDTC), DAE, Keyotkhali, Mymensingh during the period from February to May 2006. Oyster mushroom was cultivated on different substrates viz. paddy straw, sugarcane bagasse and mustard straw using cylindrical block system to find out suitable substrate. Different substrates significantly affected the number of primordia and fruiting bodies, and the amount of fresh weight or yield of Oyster mushroom in cylindrical block system. The highest number of primordia and fruiting bodies, and the amount of fresh weight was obtained with sugarcane bagasse in all flushes whereas, the lowest with mustard straw.DOI: http://dx.doi.org/10.3329/pa.v19i1.16983 Progress. Agric. 19(1): 7 - 12, 2008